PENGARUH CURRENT RATIO, RETURN ON ASSETS, DAN FIRM SIZE TERHADAP PERINGKAT OBLIGASI PADA PERUSAHAAN NON KEUANGAN DI BURSA EFEK INDONESIA PERIODE 2012-2016 - Ruli Pratiwi; V. Santi Paramita (Prosiding Working Papers Series In Management, 2018)
The purpose of this research is to analyze the influence of current ratio (RO), return on assets (ROA), and firm size of Bond Rating (PO) in non-financial companies in Indonesia Stock Exchange period 2012-2016 either partially or simultaneously. This research uses quantitative approach with multiple regression analysis. Sampling technique used is purposive sampling method that produces 9 companies as research sample. The results of this study indicate that partially Return on Assets has a significant positive effect on the rating of Bonds. Current Ratio has significant negative effect on Bond Rating. Firm Size has no significant effect on the Bond Rating. Keywords: Bond Rating (PO), Current Ratio (CR), Return on Assets (ROA), and Firm Size.